2009
DOI: 10.1016/j.peptides.2009.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric characterization and physiological actions of novel crustacean C-type allatostatins

Abstract: The crustacean stomatogastric ganglion (STG) is modulated by numerous neuropeptides that are released locally in the neuropil or that reach the STG as neurohormones. Using 1,5-diaminonaphthalene (DAN) as a reductive screening matrix for matrix-assisted laser desorption/ ionization (MALDI) mass spectrometric profiling of disulfide bond-containing C-type allatostatin peptides followed by electrospray ionization quadrupole time-of-flight (ESI-Q-TOF) tandem mass spectrometric (MS/MS) analysis, we identified and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 54 publications
2
77
0
Order By: Relevance
“…Although it was initially thought to exist solely among holometabolous insects, several recent studies have predicted and/or identified the presence of related peptides from the C-AST family in other insects and crustaceans, including decapod crustaceans Gard et al, 2009;Ma et al, 2009;Stemmler et al, 2010;Veenstra, 2009;Weaver and Audsley, 2009). Here, we found that the native H. americanus C-AST (pQIRYHQCYFNPISCF), like the C-AST-like peptide (SYWKQCAFNAVSCFamide) that was examined previously , modulates rhythmic pattern generation in the H. americanus cardiac neuromuscular system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was initially thought to exist solely among holometabolous insects, several recent studies have predicted and/or identified the presence of related peptides from the C-AST family in other insects and crustaceans, including decapod crustaceans Gard et al, 2009;Ma et al, 2009;Stemmler et al, 2010;Veenstra, 2009;Weaver and Audsley, 2009). Here, we found that the native H. americanus C-AST (pQIRYHQCYFNPISCF), like the C-AST-like peptide (SYWKQCAFNAVSCFamide) that was examined previously , modulates rhythmic pattern generation in the H. americanus cardiac neuromuscular system.…”
Section: Discussionmentioning
confidence: 99%
“…The modulatory effects of C-AST in the lobster cardiac system clearly differ in detail from these effects, as they involve changes in the cycle frequency and duration of action potential bursts in pattern-generating neurons of the lobster CG, but not changes at the muscle or neuromuscular junction. Inhibitory effects of all three AST types (A-, B-and C-types) have been documented in the pyloric pattern generator of the stomatogastric system, but details of the mechanisms used to cause the observed decreases in cycle frequency have not yet been examined Dircksen et al, 1999;Fu et al, 2007;Ma et al, 2009;Szabo et al, 2011). Additionally, inhibitory effects of A-type allatostatins have been recorded in the crab CG (Cruz-Bermudez and Marder, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Responses of individual neurons, synapses, and circuits to neuromodulation are often quite variable (50,51). In some instances, it is clear that the effect of the modulator depends on some obvious feature of the state of the preparation (52)(53)(54)(55)(56). In some instances, this variability arises from unknown sources and is likely a consequence of differing underlying cell or circuit parameters.…”
Section: Parameter Compensation and Correlationsmentioning
confidence: 99%
“…More recently, in silico database searches for putative peptide precursors or molecular cloning approaches, coupled with predictions of peptide processing, have led to the MS confirmation of the structures of novel neuropeptides, including members of the C-type allatostatin (AST) [59][60][61], orcokinin [62], pigment dispersing hormone (PDH) [63], and SIFamide [64] families (see ''Crustacean neuropeptide families'' for descriptions of these peptide groups). As mentioned above, bioinformaticsaided MS techniques are also playing an important role in large-scale neuropeptidome studies [23,25].…”
Section: Examples Of Ms-based Approaches For Crustacean Neuropeptide mentioning
confidence: 99%